Gender, Religion and Education in a Chaotic Postmodern World - Gross, Zehavit (SpringerLink Bücher, 2013)
The immense changes that the world is undergoing in terms of globalization and migration of peoples have had a profound effect on cultures and identities. The question is whether this means shifts in religious identities for women and men in different contexts, whether such shifts are seen as beneficial, negative or insufficient, or whether social change actually means new conservatisms or even fundamentalisms. Surrounding these questions is the role of education is in any change or new contradiction. This unique book enhances an interdisciplinary discourse about the complex intersections between gender, religion and education in the contemporary world. Literature in the social sciences and humanities have expanded our understanding of women's involvement in almost every aspect of life, yet the combined religious/educational aspect is still an under-studied and often under-theorized field of research. How people experience their religious identity in a new context or country is also a theme now needing more complex attention. Questions of the body, visibility and invisibility are receiving new treatments. This book fills these gaps. The book provides a strong comparative perspective, with 15 countries or contexts represented. The context of education and learning covers schools, higher education, non-formal education, religious institutions, adult literacy, curriculum and textbooks. Overall, the book reveals a great complexity and often contradiction in modern negotiations of religion and secularism by girls and boys, women and men, and a range of possibilities for change. It provides a theoretical and practical resource for researchers, religious and educational institutions, policy makers and teachers